Ultrasonographic technique and appearance of the coelomic organs in crocodilians - Yeong, Wei Yeng; Martelli, Paolo; Chung, Tabris Yik To; Tsui, Henry Chun Lok; Gerussi, Tommaso; Kot, Brian Chin Wing (Frontiers in Marine Science, 2024)
Crocodilians have significant ecological, conservational, and economic roles. They are also commonly raised for commercial purposes and kept as zoological specimens. Although ultrasonography has been used in zoological contexts for health assessments of crocodilians, published studies on a detailed ultrasonography protocol and ultrasonographic anatomy are lacking. This study aimed to establish a standardized ultrasonography protocol and pictorial reference of the ultrasonographic appearances of the coelomic organs of crocodilians. A total of 7 crocodilians comprising 4 different species were included in this study. The crocodilians were manually restrained and underwent a non-contrasted and contrasted computed tomography (CT) scan, followed by an ultrasonography (USG) examination. Ultrasound fusion imaging technique was utilized to enable greater confidence in establishing a clear organ localization and correlation between modalities by visualizing the same anatomy from the same view angle. The heart, caudal vena cava, liver, fat body (steatotheca), spleen, stomach, duodenal loops, pancreas, kidneys, testes, ovaries and cloaca were visualized in all species. Longitudinal and transverse images of the coelomic structures were acquired when possible. The ultrasonographic characteristics including transducer positioning, acoustic window and approach, shape, size, marginations, and echo pattern were documented. The findings of this study provided a useful ultrasonographic anatomical reference of the coelomic organs in crocodilians, which could provide invaluable insights into the practicality and adequacy of ultrasonography in evaluating the coelomic structures of crocodilians as part of health assessment and disease diagnosis.